Effects of Underwater Lighting Time on the Growth of Vallisneria spinulosa Yan and Its Water Restoration Process - Wei, Mengyi; Zhao, Jinshan; Zhou, Xiaolin; Li, Fengdan; Zhao, Min; Zheng, Xiangyong; Tang, Ye; Yang, Chang; Jin, Zhenmin; Wu, Suqing (Water (Basel), 2024)
Submerged macrophytes play a crucial role in the ecological restoration of water bodies, and their restoration capacity is closely related to the underwater lighting conditions. This study explored the effects of underwater lighting time on the growth characteristics of Vallisneria spinulosa Yan (V. spinulosa) and its water restoration process. V. spinulosa achieved a higher Fv/Fm (0.64), ETRmax (10.43), chlorophyll content (0.85 mg/g), and removal efficiency of total phosphorus (0.37 × 10−3 g m−3 d−1) and a lower algal abundance with a longer lighting time (18 h every day). However, a higher removal efficiency of NH4+–N and TN was obtained with a shorter lighting time (6–12 h every day). The lighting time showed a significance influence on the microbial community of the V. spinulosa growth system, and the influence was significantly different in different regions. Temperature and electrical conductivity were the main environmental impact factors for the microbial community under different lighting times. The abundances of Proteobacteria, Bacteroidota, and Verrucomicrobia exhibited a great positive correlation with each other and a strong positive correlation with the two factors. In addition, the lighting time had a strongly significant correlation with the physical and chemical characteristics of the water environment (p < 0.001) and a significant correlation with the growth characteristics of V. spinulosa (p < 0.05).